2014
DOI: 10.5114/reum.2014.47231
|View full text |Cite
|
Sign up to set email alerts
|

HELLP syndrome: a complication or a new autoimmune syndrome?

Abstract: Słowa kluczowe: zespół HELLP, powikłania ciąży, możliwości terapeutyczne. S t r e s z c z e n i eZespół HELLP (hemolysis, elevated liver enzymes, low platelets) jest schorzeniem występującym u kobiet w ciąży. Składają się na niego następujące objawy: hemoliza ze zwiększonym stężeniem dehydrogenazy mleczanowej, zwiększonym stężeniem enzymów wątro-bowych oraz obniżona liczba płytek krwi. Zespół HELLP uznawany jest za ciężką postać zaburzeń nadciśnieniowych wywołanych cią-żą, do których należą także stan przedrzu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Studies suggest that abnormalities in the metaplastic immune microenvironment may be associated with the development of RSA (Triggianese et al, 2016). However, the underlying mechanisms by which dysregulation of the meconium immune microenvironment leads to RSA are not known.…”
Section: Single-cell Rna Sequencing In Nk Cellsmentioning
confidence: 99%
“…Studies suggest that abnormalities in the metaplastic immune microenvironment may be associated with the development of RSA (Triggianese et al, 2016). However, the underlying mechanisms by which dysregulation of the meconium immune microenvironment leads to RSA are not known.…”
Section: Single-cell Rna Sequencing In Nk Cellsmentioning
confidence: 99%
“…Studies in humans reported that absolute counts of B cell peripheral compartment in the last trimester of pregnancy and in term decidua are decreased in comparison to non-pregnant controls (130,131). HELLP is not typically described as an autoimmune disorder, however, it is highly prevalent in pregnant women with autoimmune diseases such as acute phospholipid syndrome, systemic lupus erythematosus and thrombotic thrombocytopenic purpura (132)(133)(134)(135). To what degree antibodies can play a role in HELLP pathogenesis is still questionable.…”
Section: B Cells In Hellpmentioning
confidence: 99%